A Novel Inflammatory Dendritic Cell That Is Abundant and Contiguous to T Cells in the Kidneys of Patients With Lupus Nephritis - Parikh, Samir V.; Malvar, Ana; Shapiro, John; Turman, James M.; Song, Huijuan; Alberton, Valeria; Lococo, Bruno; Mejia-Vilet, Juan M.; Madhavan, Sethu; Zhang, Jianying; Yu, Lianbo; Satoskar, Anjali A.; et al. (Frontiers in Immunology, 2021)
The mechanisms that promote local inflammatory injury during lupus nephritis (LN) flare are largely unknown. Understanding the key immune cells that drive intra-renal inflammation will advance our knowledge of disease pathogenesis and inform development of new therapeutics for LN management. In this study, we analyzed kidney biopsies from patients with proliferative LN and identified a novel inflammatory dendritic cells (infDC) population that is highly expressed in the LN kidney, but minimally present in healthy human kidneys. During an agnostic evaluation of immune transcript expression in kidneys of patients with proliferative LN, the most abundantly over-expressed transcript from isolated glomeruli was found to be FCER1G, which encodes the Fc receptor gamma chain (FcRγ). To identify the cell types expressing FcRγ that infiltrate the kidney in LN, studies were done on kidney biopsies from patients with active LN using confocal immunofluorescence (IF) microscopy. This showed FcRγ to be abundantly present in the periglomerular (PG) region of the kidney, and to a lesser extent in the tubulointerstitium (TI). Further investigation of the surface markers of these cells showed that they were FcRγ+, MHC II+, CD11c+, CD163+, CD5-, DC-SIGN+, CD64+, CD14+, CD16+, SIRPα+, CD206-, CD68-, CD123-, CD3-, CD11b-, suggesting the cells were infDC. Quantification of infDC showed an average 10-fold higher level of infDC cells in the LN kidney compared to healthy kidneys. Importantly, IF identified CD3+ T cells to be adjacent to these infDC in the PG space of the LN kidney, whereas both cell types are minimally present in healthy kidney. Thus, we have identified a previously undescribed DC in lupus kidneys that may interact with intra-renal T cells and play a role in the pathogenesis of kidney injury during LN flare.